New insights in large-pores mesoporous silica microspheres for hemostatic application - Sara Saber Younes Mohamed; Roberta Cavalli; Elisabetta Rombi; Luciano Atzori; Marco Armandi; Barbara Onida (Journal of Materials Science: Materials in Medicine)
Abstract Hemorrhages are still considered a common cause of death and despite the availability of different hemostatic agents it is still necessary to develop more effective hemostats for bleeding managements in emergency situations. Herein, large-pores mesoporous silica microspheres (MSM) were synthesized, and their surface was modified to enrich the hydroxyls population with the aim of achieving a material with enhanced water adsorption capacity and high hemostatic ability. The success of surface modification was investigated by Fourier Transform Infrared spectroscopy (FT-IR) and thermogravimetric analysis (TGA), which confirmed the increase in the amount of surface hydroxyl groups. A hemolysis assay as well as a clotting test were carried out to evaluate the hemocompatibility and hemostatic ability, respectively. It was found that the modified material presented the lowest hemolytic ratio and the lowest clotting time. The novelty of the paper is mainly due to the coupling of the hemostatic ability test with the adsorption microcalorimetry of water. In fact, being the water adsorption on the material surface a crucial factor in the hemostatic activity, microcalorimetry was used for the first time to study the adsorption of water and estimate its heat of adsorption. The data obtained showed that the modified MSM presents a surface able to adsorb a higher amount of water, compared to the pristine MSM, with a low molar heat of adsorption (about 35 kJ/mol), which renders the modified MSM presented in the present study an excellent candidate for producing novel hemostats. Graphical Abstract